The Dilemma of Students in the Age of AI: Analysis of the Effects of ChatGPT Use and Academic Procrastination - Maheswari Ayu Pratiwi; Wiwik Juwarini Prihastiwi (P3I UMSurabaya, 2025)
The development of artificial intelligence (AI) has changed the way students interact with academic processes, especially through the use of Generative AI such as ChatGPT. This study aims to analyze the relationship between the intensity of ChatGPT use and the level of academic procrastination among students. The study used a descriptive quantitative approach with accidental sampling of 100 students at Muhammadiyah University Surabaya. The research instruments were the ChatGPT Usage Scale, adapted from the academic technology usage intensity scale, and the Procrastination Assessment Scale for Students (PASS) version by Jannati (2020). The analysis results show a significant positive relationship between ChatGPT usage and academic procrastination (r = 0.646; p < 0.001), with an effective contribution of 41.7% (R² = 0.417). This indicates that the higher the intensity of ChatGPT usage, the higher the tendency to delay academic tasks.